ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPATUHAN WAJIB PAJAK BADAN DALAM MEMENUHI KEWAJIBAN PERPAJAKAN (DALAM PERSPEKTIF TAX PROFESSIONAL) (Studi Pada Wajib Pajak Badan Yang Terdaftar Di KPP Madya Pekanbaru) - Mariana br Purba; Zirman '; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to Analysis Thefactors that affect tax compliance on corporate taxpayers registered in KPP Madya Pekanbaru. Variables to be tested in this research is attitude of tax professional, subjective norm, perceived behavior control, financial condition, corporate facilities, organizatinal climate and tax compliance. The data in this research is primary data obtained from questionnaires distributed directly to the respondents. Respondents in this study is a tax professional who works at a company registered in KPP Madya Pekanbaru who have served a minimum of 1 year and ever filled out tax returns. Data collected from 92 respondents. In this study, the data obtained will be processed by multiple linear regression models (multiple regression).The results show that the attitude of tax professional bring a significant that affect on corporate tax compliance with a significant value 0,020 (alpha 0,05). Subjective norm affect on corporate tax compliance with significant value 0,013. Perceived behavior affect on corporate tax compliance with a significant value 0,005. Financial condition affect on corporate tax compliance with significant value 0,046. Corporate facilities affect on corporate tax complince with significant value 0.009. Organizational climate has a positive affect partially on corporate tax compliance, with significant value 0,031.Keywords : Planned Behavior, Financial, Corporate Facilities, Organizational and Tax Compliance.